Women's Representation on Regional People's Representative Council Padang City in Society Homogeneity - Lince Magriasti; Nur Iman Subono; Meidi Kosandi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
This research aims to describe the process of nominating women for political parties and the electability of women in the regional representative council Padang City as seen from the 2014 and 2019 elections. Using the concept of Pitkin's descriptive political representation simplified by Phillips as a politics of presence, this paper describes women's electability in the Padang legislature with homogeneous community conditions with majority ethnicity are Minangkabau. The presence of women candidates in the Padang City legislature has benefited from the economic conditions owned both individually and by families. Political factors also show that there's still the influence of family politics in the candidacy of women. The level of incumbent electability was high from the 2014 to 2019 elections, but in quantity, there was a decrease in women's representation in the Padang City legislature. Meanwhile, if we look at the homogeneity of the people in Padang, conditions also follow it in the Padang legislature, which is also filled with representatives of women from Minangkabau ethnicity. However, this community homogeneity does not increase women in political institutions.